Designing a Female Hero Educational Game using Adobe Animate and the ADDIE Method - Sembiring, Asha; Sagala, Alon Jala Tirta; Yahaya, Wan Ahmad Jaafar Wan (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2024)
Many do not know that heroes in Indonesia are not only men but women who also participate in the struggle and act as heroes in Indonesia. Female heroes are also very instrumental for Nusa and the Nation. Technology development is now increasingly advanced. For example, mobile phones are owned by every group, such as children, teenagers to the elderly. Mobile phones can also be used as entertainment media such as games that can increase children’s interest in learning who tend to like animated images and can increase knowledge, so education is not too saturated. This study aims to develop an educational game that can introduce national female heroes using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) method. This development method focuses on iteration and reflection, so continuous improvement can be made that focuses on feedback. Using a questionnaire, software testing techniques focused on functional specifications and usability testing on a Likert scale. Blackbox testing can provide an overview of the program combined state and perform functional testing. Likert scale questionnaire testing can produce as expected. The result of the research is an educational game introducing the heroine, which is expected to be used to introduce the national heroine to children and students.